2021
DOI: 10.1128/jvi.01564-20
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Interferon-Inducible GTPase GBP1 as a Major Restriction Factor for Hepatitis E Virus

Abstract: This study aims to gain deeper insight into HEV-induced innate immunity by characterizing the crosstalk between the virus and the host factor guanylate-binding protein 1 (GBP1). We observe that the amount of GBP1 is elevated upon infection, although number of transcripts is decreased, which is explained by a prolonged protein half-life. Modulation of GBP1 levels via overexpression significantly inhibits the viral life cycle. Use of various GBP-1 mutants revealed that the antiviral effect of GBP-1 on HEV is ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 57 publications
2
25
0
Order By: Relevance
“…For KSHV, the transport of the viral capsid to the nucleus is hampered by disruption of the actin filaments by hGBP1 [ 38 ]. HEV is inhibited through the relocation of the capsid protein by hGBP1 to the lysosome [ 39 ]. For HCV, the observed interaction with RNA-dependent RNA polymerase NS5B could be a possible explanation for the viral restriction [ 40 ].…”
Section: Gbp Functions In Plants Invertebrates and Vertebratesmentioning
confidence: 99%
“…For KSHV, the transport of the viral capsid to the nucleus is hampered by disruption of the actin filaments by hGBP1 [ 38 ]. HEV is inhibited through the relocation of the capsid protein by hGBP1 to the lysosome [ 39 ]. For HCV, the observed interaction with RNA-dependent RNA polymerase NS5B could be a possible explanation for the viral restriction [ 40 ].…”
Section: Gbp Functions In Plants Invertebrates and Vertebratesmentioning
confidence: 99%
“…Very recently, the role of this antiviral factor against HEV was established. Authors revealed that GBP1 exerted its antiviral role by the homodimerization and independent of GTPase activity wherein GBP1 targeted virus to the lysosomal compartment to inactivate it [72].…”
Section: Induction Of Interferon Stimulated Genes (Isgs) By Hevmentioning
confidence: 99%
“…There are 7 GBPs in human that are involved in various cellular functions such as inhibition of cell spreading and proliferation, activation of inflammosome and antimicrobial activities against viruses, bacteria and protozoans ( Vestal and Jeyaratnam, 2011 ; Kravets et al., 2016 ; Wandel et al., 2017 ; Tretina et al., 2019 ; Yu et al., 2020 ). In addition to their established role in host resistance to bacterial and protozoal pathogens, GBPs (e.g., GBP1, GBP2 and GBP5) been have shown to have antiviral activity against human immunodeficiency virus (HIV), Zika virus (ZIKV), hepatitis C virus (HCV), classical swine fever virus (CSFV), dengue virus (DENV), murine norovirus (MNV), influenza virus, hepatitis E virus (HEV), vesicular stomatitis virus (VSV) and encephalomyocarditis virus (EMCV) ( Anderson et al., 1999 ; Nordmann et al., 2012 ; Pan et al., 2012 ; Krapp et al., 2016 ; Li et al., 2016 ; Yu et al., 2020 ; Glitscher et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%